Inclusivity or division? The unintended consequences of non-segregated gyms - Mohamad Shukri, Syaza Farhana (ISEAS - Yusof Ishak Institute, 2024)
An increased amount of attention has been paid to the dynamics that exist inside public spaces as society continues to make progress towards equality and inclusivity. A powerful illustration of this is in Malaysia, where student activists from the University of Malaya have opposed rules for segregated gym hours. The students’ use of religiously-charged terms against segregation in public spaces belies the fact that there are rational and reasonable reasons for such practices.